DESAIN MODUL SWITCH SELECTOR UNTUK PENGGUNAAN REMOTE CONTROL PADA MULTIDISPLAY DIGITAL SIGNAGE BERBASIS MULTIPLEXER - Mulyo, Alfina Putri; Setyaningsih, Endah (Universitas Lampung, 2024)
Digital signage is an electronic device that can display information or announcements digitally. The choice of device depends on the characteristics of the place where the digital signage is placed. Restaurants are one of the places where a large number of digital signage is used. The large number of digital signage can extend the display setting time of digital signage displays. The large number of digital signage units used can also affect the number of remotes used, making it less efficient when setting up displays. Therefore, this design is made to make it easier for users to choose which digital signage display they want to set. This design is in the form of a selector module called a multiplexer-based switch selector module. This module consists of a toggle switch, multiplexer, and infrared receiver as the main components and has 4 output channel which can connect with 4 display digital signage. Tests are carried out using 1 digital signage in rotation for each channel. Digital signage display can respond to the signal emitted by the remote via an infrared receiver connected to the module. Therefore, it can be concluded that the switch selector module in the use of remote control can function properly.